Picosecond supercontinuum generation seeded by a weak continuous wave - 李荧 侯静 冷进勇 王文亮 姜宗福 (Chinese physics B, 2013)
We experimentally investigate the spectral details of a picosecond supercontinuum pumped at 1064 nm and seeded by a weak continuous wave （～20000 times weaker than the pulse peak power） at several power levels in photonic crystal fibers. Seeding at different wavelengths leads to different spectral details and the effects to the bandwidth of supercontinuum are also distinct. Spectra can be widened when seeded by a continuous wave at 1070 nm and narrowed by ～100 nm when seeded at 1080 nm. The influence is enhanced by increasing the average seeded power.